Pork Ham and Belly Processing Traits With Increasing Carcass Weight - Bailey Harsh; Dani C Shirey; Erin Bryan; Hannah Marie Remole; Joseph Lee Metz; Kaitlin Richey Guthrie; Kayla E Barkley; Khalil Atef Jallaq; Xuenan Chen (Meat and Muscle Biology)
The objective of this study was to determine the effect of increasing hot carcass weight (HCW) on pork ham and belly processing characteristics. Pigs (n = 85) were slaughtered and divided into 3 HCW categories: Average (99 to 109 kg), Heavy (116 to 126 kg), and Very Heavy (134 to 144 kg). Fresh hams were fabricated and further processed as 3-piece (inside, outside, and knuckle) boneless cured hams. Fresh belly quality measurements were taken before bacon processing. Data were analyzed using the MIXED procedure in SAS including the main effect of weight class, with sex and sire line as random blocking effects. Means were considered significant at P ≤ 0.05. There were no differences (P = 0.08) in ham processing characteristics including pump uptake, retention, and cook yield. However, cured hams from heavier car- casses were less red and less yellow (P < 0.01). Heavier carcasses produced longer, thicker, and wider bellies (P < 0.01), but bellies did not differ in firmness (P = 0.16). Despite reduced pump uptake (P < 0.01), bellies from heavier carcasses had greater cooked yield than those from lighter carcasses (P < 0.01). Total area of sliced bacon increased with increasing carcass weight. Bacon slice lean area percentage decreased (P < 0.01) in bacon from Very Heavy carcasses compared to lighter carcasses. Iodine value was decreased (P = 0.04) approximately 2.5 units from 68.6 in fresh bellies from Average carcasses to 66.2 in bellies from Very Heavy carcasses. Overall, processing characteristics of hams and bellies were not impaired at heavier carcass weights, though the consumer acceptability of larger slices of bacon from heavier carcasses should be determined.